Physiologic musculofascial compliance following reinforcement with electrospun polycaprolactone-ureidopyrimidinone mesh in a rat model - Hympanova, Lucie; Mori da Cunha, Marina Gabriela Monteiro Carvalho; Rynkevic, Rita; Zündel, Manuel; Gallego, Monica Ramos; Vange, Jakob; Callewaert, Geertje; Urbankova, Iva; Van der Aa, Frank; Mazza, Edoardo; Deprest, Jan (Journal of the mechanical behavior of biomedical materials, 2017)
PURPOSE: Electrospun meshes may be considered as substitutes to textile polypropylene implants. We compared the host response and biomechanical properties of the rat abdominal wall following reinforcement with either polycaprolactone (PCL) modified with ureidopyrimidinone-motifs (UPy) or polypropylene mesh. METHODS: First we measured the response to cyclic uniaxial load within the physiological range both dry (room temperature) and wet (body temperature). 36 rats underwent primary repair of a full-thickness abdominal wall defect with a polypropylene suture (native tissue repair), or reinforced with either UPy-PCL or ultra-light weight polypropylene mesh (n = 12/group). Sacrifice was at 7 and 42 days. Outcomes were compliance of explants, mesh dimensions, graft related complications and semi-quantitative assessment of inflammatory cell (sub) types, neovascularization and remodeling. RESULTS: Dry UPy-PCL implants are less stiff than polypropylene, both are more compliant in wet conditions. Polypropylene loses stiffness on cyclic loading. Both implant types were well incorporated without clinically obvious degradation or herniation. Exposure rates were similar (n = 2/12) as well as mesh contraction. There was no reinforcement at low loads, while, at higher tension, polypropylene explants were much stiffer than UPy-PCL. The latter was initially weaker yet by 42 days it had a compliance similar to native abdominal wall. There were eventually more foreign body giant cells around UPy-PCL fibers yet the amount of M1 subtype macrophages was higher than in polypropylene explants. There were less neovascularization and collagen deposition. CONCLUSION: Abdominal wall reconstruction with electrospun UPy-PCL mesh does not compromise physiologic tissue biomechanical properties, yet provokes a vivid inflammatory reaction.
Keywords: Animals; kosterní svaly; chirurgické síťky; Biocompatibility; Female; Biomechanics; Hernia; Electrospun mesh; ženské pohlaví; Abdominal Wall; Fascia; pyrimidinony; Muscle, Skeletal; Polyesters; Pelvic organ prolapse; Rats, Sprague-Dawley; biomechanika; fascie; potkani Sprague-Dawley; krysa rodu Rattus; Pyrimidinones; zvířata; polyestery; Surgical Mesh; Rats; Biomechanical Phenomena; břišní stěna